Penggunaan Media Puzzle Lantai Untuk Meningkatkan Kemampuan Mengenal Huruf Pada Anak Kelompok B Di Tk Gmim Eben Haezer Kapataran - Lotulung, Indra Liny (Jurnal Ilmiah Wahana Pendidikan, 2023)
The background to this research is the low ability to recognize letters in children at the GMIM Eben Haezer Kapataran Kindergarten. The aim of this research is to describe the use of floor puzzle media to improve the ability to recognize letters. The research method used is Classroom Action Research model Kemmis and Mc. Taggart is carried out twice in cycles with the steps namely planning, implementation, observation and reflection. The subjects of this research were 22 children from GMIM Eben Haezer Kapataran Kindergarten Group B. The data collection techniques used were observation and field notes as well as data analysis using assessment techniques in kindergarten. The results of the research showed that cycle I was 59% and cycle II had increased after improvements were made to 100%. It was concluded that the use of floor puzzle media can improve the ability to recognize letters in children at the GMIM Eben Haezer Kapataran Kindergarten